Axial Length as the Primary Determinant of Refractive Severity in High Myopia: A Swept-Source OCT Analysis - Hafiz Shatari; Rinda Wati (HM Publisher, 2026)
Background: The escalating prevalence of high myopia represents a critical global health crisis, particularly in Southeast Asia. This pathological refractive status is driven by complex structural changes, primarily axial elongation, which predisposes the eye to sight-threatening complications. While the dominance of axial length in myopia is established, the compensatory role of the anterior segment—specifically whether the cornea or anterior chamber undergoes adaptive morphological changes to counteract elongation—remains a subject of debate. This study utilized high-resolution Swept-Source Optical Coherence Tomography (SS-OCT) to precisely quantify the relationship between Spherical Equivalent (SE) and ocular biometric parameters, isolating the specific contributions of posterior segment elongation versus anterior segment adaptation. Methods: This observational analytic study with a cross-sectional design was conducted at the Ophthalmology Clinic of Dr. M. Djamil General Hospital, Padang, Indonesia. The study recruited patients aged 18–40 years diagnosed with high myopia (SE defined as -6.00 Diopters or worse). Strict exclusion criteria were applied to eliminate confounding anterior segment pathologies. Ocular biometry was performed using the IOLMaster 700, which employs Swept-Source OCT technology for full-eye length tomography. We analyzed Axial Length (AL), Mean Keratometry (K), Central Corneal Thickness (CCT), and Anterior Chamber Depth (ACD). Statistical analysis utilized Pearson and Spearman correlation tests and linear regression modelling. Results: A total of 32 eyes from 32 high myopia patients were analyzed. The mean SE was -8.14 plus or minus 2.09 D, and the mean AL was 26.93 plus or minus 1.92 mm. We found a robust, statistically significant negative correlation between SE and AL (r = -0.86; p less than 0.001), confirming AL as the primary determinant of refractive severity. Notably, a moderate negative correlation was observed between AL and K (r = -0.41; p = 0.02), indicating a paradoxical corneal flattening in longer eyes. No significant correlations were found between SE and CCT or ACD. Conclusion: Axial elongation is the predominant structural mechanism driving high myopia in this cohort. The study identified a distinct compensatory response where the cornea flattens as the eye elongates; however, this emmetropization mechanism is insufficient to neutralize the profound refractive shift caused by posterior segment expansion. These findings suggest that high myopia is a disease of focal posterior scleral remodelling rather than global ocular expansion.